2010
DOI: 10.1007/bf03326167
|View full text |Cite
|
Sign up to set email alerts
|

Study of mango biomass (Mangifera indica L) as a cationic biosorbent

Abstract: Unfertilizable fruiting buds of mango plant Mangifera Indica L, an agrowaste, is used as a biomass in this study. The efficacy of the biosorbent was tested for the removal of lead, copper, zinc and nickel metal ions using batch experiments in single and binary metal solution under controlled experimental conditions. It is found that metal sorption increases when the equilibrium metal concentration rises. At highest experimental solution concentration used (150 mg/L), the removal of metal ions were 82.76 % for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…The influence of initial concentration on uptake capacities of Cu(II) and Zn(II) was studied by dead hybrid immobilized biosorbent of P. sajor-caju and J. sambac at pH 5 and 6 for Cu(II) and Zn(II), respectively, by changing the concentration of the system from 25 to 800 mg/L. Results obtained in this study showed that there is a linear relationship between sorption capacity and initial metal ion concentration, and this is also supported by the literature (Ashraf et al 2010). This study also depicted an inversely proportional relationship between percentage removal and initial metal concentration, as reported previously (Bai et al 2010).…”
Section: Effect Of Initial Metal Concentrationsupporting
confidence: 86%
See 1 more Smart Citation
“…The influence of initial concentration on uptake capacities of Cu(II) and Zn(II) was studied by dead hybrid immobilized biosorbent of P. sajor-caju and J. sambac at pH 5 and 6 for Cu(II) and Zn(II), respectively, by changing the concentration of the system from 25 to 800 mg/L. Results obtained in this study showed that there is a linear relationship between sorption capacity and initial metal ion concentration, and this is also supported by the literature (Ashraf et al 2010). This study also depicted an inversely proportional relationship between percentage removal and initial metal concentration, as reported previously (Bai et al 2010).…”
Section: Effect Of Initial Metal Concentrationsupporting
confidence: 86%
“…This study also depicted an inversely proportional relationship between percentage removal and initial metal concentration, as reported previously (Bai et al 2010). When metal ions at very low concentration are applied to biosorbent, then greater metal uptake occurs, because large number of vacant sorption sites is available for metal binding (Ashraf et al 2010). At higher concentration, low-metal uptake may be attributed to saturation of sorption sites.…”
Section: Effect Of Initial Metal Concentrationmentioning
confidence: 99%
“…Pineapple (Ananas comosus), belonging to Bromeliaceae family, is a kind of perennial monocotyledon herbaceous plant as well as one of the most known tropical fruits [1]. In China, pineapple is mainly planted in 6 provinces including Hainan, Guangdong, Guangxi, Yunnan, Fujian, and Taiwan.…”
Section: Introductionmentioning
confidence: 99%
“…They are potential biosorbents due to the presence of numerous functional groups serving as binding sites for adsorption. A wide range of natural biomass has been studied as biosorbents (Lau et al 2003;Ashraf et al 2011aAshraf et al ,b, 2012Hossain et al 2012;Achak et al 2009;Chuah et al 2005;Saha et al 2013;Contreras et al 2012;Kiran et al 2013;Singha and Das 2012). Bhatnagar et al (2010) provides a comprehensive review of the use of coconut-based biomass as biosorbents, as which they are extensively applied for heavy metals and dyes.…”
Section: Introductionmentioning
confidence: 99%